Microstructure and dosimetric characterisation of delaminated film dosimeter under 12 MeV electron beam. (March 2020) - Tagiling, N; Khairil Anuar, MA; Ab Rashid, R; Dollah, N; Rahman, WN
Abstract: Delaminated GAFCHROMIC™ EBT3 radiochromic films (RCFs) are specialised dosimeters that are gaining attention due to its many prospective advantages but are not commercially available. The purpose of this study is to fabricate the delaminated EBT3 RCFs, microscopically examine the structural response of the active layer (LiPCDA), and evaluate its dose-response in electron beam radiotherapy. The delaminated EBT3 RCFs were first made by carefully removing one of the two 125 μm polyester substrates using precision forceps. Next, the films were irradiated using a 12 MeV electron beam under full equilibrium conditions. Microstructure analysis via scanning electron microscope (SEM) was employed to look into the effects of radiation polymerisation on the LiPCDA crystals at 3000× magnification. To characterise the dose-response, the delaminated EBT3 RCFs' optical density were analysed in Red-channel across a dose range of up to 5 Gy. The resulting calibration curve was then compared with the standard EBT3 RCFs' curve for performance evaluation. Images from SEM revealed that the irradiated EBT3 RCF possesses a higher density of longer LiPCDA crystals (mode: ∼8.00 μm) compared to the non-irradiated EBT3 RCF (mode: ∼4.00 μm). The delaminated EBT3 RCFs, nonetheless, was found to produce a combined standard uncertainty of 6.62 %, which is inferior to its standard counterpart (3.62 %) and also the radiotherapy's tolerance level (± 5 %). In sum, this study had successfully demonstrated the effects of radiation polymerisation on the active layer. However, the delamination process introduced a significant amount of uncertainty towards the dose-response. More efforts into delamination techniques and better dosimetry analysis are required to improve its usability in radiotherapy.